A static and mystical karma, and an amazing poetic growth. - Abdulmajid, L. Ala Dara Abdulmajid (Sulaimani Journal for Humanities, 2025)
In the tired world of technology, human existence as an active part of it is a momentary happiness and a permanent regret because it has been used psychologically Temporary reinforcers and pleasures. Strength has been weakened in man, in the face, in the arms, in the mines of emotion, in the expression of conscience and in the emotions of the heart and mind. There have been attempts to regain strength and fill this gap at various levels. Some have resorted to nature, some in the shadow of invented beliefs, and some have even turned to aggression to achieve this goal. Then under many terms, programs and complex, secret and open work. The search for spiritual strength and the correction of the death of conscience and the unperceived positivity of people has been attempted. Karma or the ability and power of the soul that varies from person to person and from one bearer of an idea to another. It has been worked on in today's world. There has been strength from sight, contemplation, beloved existence. Here, in this study, we take karma from the basis of literary thought and look at literature as a powerful spiritual enabler. Then we will find the uniqueness, liberation and height of this force and give it to the weakest, the most intellectual and mental foundations to make a program to deliver its service. Hence, better than we have known literature, we must look at it anew as a source of positive karma. From the kind of literature, ideas and the kind of karma he gets. The literature of the poet Rumi is a treasure trove of true and heavenly spiritual power from which we can obtain positive aesthetic karma.
Keywords: Literature; Philosophy of Spiritual Power Jalal; Poetry; mawlawi